A rink-amide soluble support: high purity conotoxins and other peptides accessed with minimal reagents. Issue 30 (22nd July 2019) - Bisht, Babita; Naganna, Nimmashetti; Madhavan, Nandita
Abstract : The support reported here is used to synthesize difficult peptides and conotoxins using only 1.2–2 equiv. of coupling reagents. Abstract : The use of peptides as therapeutics has been growing due to their biocompatibility. Solid phase peptide synthesis typically used to access these peptides requires excess reagents and/or microwave irradiation to drive reactions to completion because the reaction medium is heterogeneous. Reported herein is a soluble polynorbornene support containing rink amide attached sites for synthesizing oligopeptides and conotoxins in high purity using only 1.2 to 2 equivalents of coupling reagents. The support can be isolated as a precipitate from the reaction medium by adding ether. The loading capacity of the support can be easily determined by spectroscopy and can also be tuned by varying the monomer ratio. This support is promising for accessing peptides as the methodology uses minimal reagents and by-products can be easily separated.